In Vitro Synergy of Pongamia pinnata Extract in Combination with Antibiotics for Inhibiting and Killing Methicillin-Resistant Staphylococcus aureus - Po-An Su; Shun-Lai Li; Hung-Jen Tang; Chi-Chung Chen; Ying-Chen Lu; Kuo-Chen Cheng; Yi-Chung Lin; Yin-Ching Chuang; Chih-Cheng Lai (MDPI AG, 2020)
Aims: Currently, we face the serious problem of multiple drug-resistant pathogens. The development of new antimicrobial agents is very costly and time-consuming. Therefore, the use of medicinal plants as a source of alternative antibiotics or for enhancing antibiotic effectiveness is important. Methods: The antibacterial effects of aqueous extracts of the seed coat of Pongamia pinnata (Linn.) Pierre in combination with several antibiotics against methicillin-resistant Staphylococcus aureus (MRSA) were tested by broth dilution, checkerboard, and time-kill methods. Results: For the combinations of P. pinnata with ampicillin, meropenem, cefazolin, cefotaxime, cefpirome, and cefuroxime, 70% to 100% were synergistic, with a fractional inhibitory concentration (FIC) index of < 0.5. For the time-kill method with 0.5× minimum inhibitory concentration (MIC) of P. pinnata in combination with 8, 4, 2, and 1 µg mL−1 of the various antibiotics, almost all of the combinations showed synergistic effects, even with the lowest concentrations of P. pinnata, except for aztreonam. No antagonistic effect was observed for these combinations. Conclusions: Based on these findings, aqueous seed coat extracts of P. pinnata have good potential for the design of new antimicrobial agents.